This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: A P = ± 1 + r m ² mt ln ± A P ² = mt ln ± 1 + r m ² . Then divide both sides by m ln ± 1 + r m ² to get ln( A P ) m ln(1 + r m ) = t. 4. Solve for r : A = Pe rt Solution: Try these steps on your own. First, divide both sides by P . Second, take the natural logarithm of both sides. Last, divide both sides by t . Your ﬁnal solution should be 1 t ln ± A P ² = r....
View Full Document
- Spring '08
- Calculus, Natural logarithm, Logarithm, Common logarithm